IMPLEMENTASI TEKNOLOGI UNTUK PENGUATAN KEAMANAN DATA PRIBADI NASABAH DALAM SEKTOR PERBANKAN - Syakira Edriamarsha Firdaus; Syarifaatul Hidayah; Herjuno Putro (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rapid technological developments have brought major transformation in the banking sector, especially in the aspect of digitalization of services. However, this progress is accompanied by big challenges, especially regarding the security of customers' personal data which is vulnerable to cyber threats. This article discusses various technologies used by banks to protect customer data, such as data encryption, fintech technology, and the implementation of cloud-based security systems. Apart from that, this article also discusses regulations governing personal data protection in Indonesia, such as Law no. 27 of 2022, as well as Financial Services Authority (OJK) regulations. The research method used is normative juridical with a conceptual and technological approach. Even though various technologies have been implemented, various challenges remain. Therefore, the banking sector also needs to continue to improve its security system. This effort is expected to create a safer banking system and increase public trust in digital banking services.